Family-based treatment for transition age youth: the role of expressed emotion and general family functioning. Issue 5 (3rd September 2019) - Dimitropoulos, Gina; Landers, Ashley L.; Freeman, Victoria; Novick, Jason; Cullen, Olivia; Le Grange, Daniel
ABSTRACT: The aim of this study was to investigate changes in family functioning and parental expressed emotion (EE) in parents and transition age youth (18 to 25 years old) with Anorexia Nervosa participating in Family-Based Treatment for Transition Age Youth (FBT-TAY). Further, we examined whether perceived family functioning and EE were associated with changes in eating disorder behaviour and weight in participants at end-of-treatment and three months post-treatment. Generalized estimating equations revealed that changes in family functioning significantly improved from baseline to end-of-treatment ( p  = .0001), and baseline to three months post-treatment ( p  = .0001) in parents; and from baseline to end-of-treatment ( p  = .011), and baseline to three months post-treatment ( p  = .0001) in transition age youth. The level of parental EE did not differ significantly from baseline to end-of-treatment ( p  = .379), or baseline to three months post-treatment ( p  = .185). A series of Ordinary Least Square regression models demonstrated that changes in perceived family functioning and EE were not significantly associated with changes in eating disorder behaviour and weight restoration of transition age youth at end-of-treatment and three months post-treatment. Overall, perceptions of family functioning improved during the course of FBT-TAY, but EE did not.